Genotoxic impurities in pharmaceutical products – regulatory, toxicological and pharmaceutical considerations - Regulska, Katarzyna; Michalak, Marcin; Murias, Marek; Stanisz, Beata (Journal of Medical Science, 2021)
This article provides an overview of the most important aspects around the detecting and reporting of genotoxic impurities in the pharmaceutical industry. It focuses on relevant regulatory, toxicological, and pharmaceutical considerations. In this regard, the concept of Threshold of Toxicological Concern is explained and the most common genotoxic impurities are described. Furthermore, toxicological methods for genotoxic impurities screening are presented. Finally, the article emphasises several issues regarding further development.